Examining the social origins and young adult life trajectories of high traditional masculinity (HTM) males: A group at elevated suicide risk. Issue 4 (6th April 2021) - Feigelman, William; Coleman, Daniel; Rosen, Zohn
Abstract: Objective: We investigated whether male high school students displaying high traditional masculinity (HTM), defined briefly as overacting male roles, possessed distinctive social origins and adult lifestyle trajectories differentiating them from others. Method: Based upon four survey waves of the National Longitudinal Study of Adolescent to Adult Health cross‐linked to the National Death Index, we contrasted surveys 1 and 2 respondents reporting HTM, n  = 3138, 31%, with the remaining 69% ( n  = 6849) on various sociodemographic characteristics, problem behaviors, suicides, and other premature mortalities. Results: High traditional masculinity males showed higher suicide rates, but no other differences in premature mortalities, compared with non‐HTM peers. More likely to be White, younger, less close to their fathers, they were more likely to run away from home, get into fights, act delinquently, and engage in problem drinking and drug use. At survey wave 3, more had been arrested. By wave 4, when approaching their early thirties, HTM males showed higher drug uses, more delinquency, completed less schooling, and were less likely to marry. Conclusions: These data not only suggest higher suicide risks among this population after high school, but judging from the durability of HTM characteristics, but also they appear at risk of "deaths of despair" during later life.